2019
DOI: 10.1002/ptr.6332
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroartemisinin, an antimalarial drug, induces absent in melanoma 2 inflammasome activation and autophagy in human hepatocellular carcinoma HepG2215 cells

Abstract: As an effective antimalarial drug, Dihydroartemisinin (DHA) is readily isolated from the traditional Chinese medicine of Artemisia annua. DHA is not only an autophagy promoter but also a substance with strong antitumor efficiency. The relationship between autophagy and inflammasomes has been suggested in hepatocellular carcinoma (HCC). However, there are few reports describing relationships between inflammasomes and autophagy in HCC therapy. The present study demonstrated that DHA suppressed cell proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 54 publications
(88 reference statements)
0
43
0
Order By: Relevance
“…Our previous studies have confirmed that DHA leads to autophagy and the death of human tongue squamous cell carcinoma (TSCC) cells in vitro and in vivo [18]. Recently, our group showed that DHA induces the activation of AIM2 inflammasome in HepG2215 cells of human hepatocellular carcinoma and autophagy in HeLa cells [19,20]. DHA has selective toxicity to tumor cells and is likely to become an anticancer drug with low toxicity, high efficiency and low cost [21,22].…”
Section: Introductionmentioning
confidence: 81%
“…Our previous studies have confirmed that DHA leads to autophagy and the death of human tongue squamous cell carcinoma (TSCC) cells in vitro and in vivo [18]. Recently, our group showed that DHA induces the activation of AIM2 inflammasome in HepG2215 cells of human hepatocellular carcinoma and autophagy in HeLa cells [19,20]. DHA has selective toxicity to tumor cells and is likely to become an anticancer drug with low toxicity, high efficiency and low cost [21,22].…”
Section: Introductionmentioning
confidence: 81%
“…For example, the suppression of IL-1β secretion by inhibiting in ammasome is expected to become a new treatment strategy in melanoma [20]. In addition, assembled in ammasomes can activate caspase-1 and cause IL-1β to be secreted from cancer cells [21]. In the present study, it was rst found that in Hep-2 cancer cells, caspase-1 was involved in the processing and secretion of IL-1β by DDP treatment in vivo.…”
Section: Discussionmentioning
confidence: 52%
“…Our previous studies have confirmed that DHA lead to autophagy and the death of human tongue squamous cell carcinoma (TSCC) cells in vitro and in vivo [19]. Recently, our group showed that DHA induces activation of AIM2 inflammasome in HepG2215 cells of human hepatocellular carcinoma and autophagy in HeLa cells [20,21]. DHA has selective toxicity to tumor cells and is likely to become an anticancer drug with low toxicity, high efficiency and low cost [22,23].…”
Section: Introductionmentioning
confidence: 78%